Structural Basis of Lipid Targeting and Destruction by the Type V Secretion System of Pseudomonas aeruginosa. Issue 9 (8th May 2016) - da Mata Madeira, Paulo Vinicius; Zouhir, Samira; Basso, Pauline; Neves, David; Laubier, Aurélie; Salacha, Richard; Bleves, Sophie; Faudry, Eric; Contreras-Martel, Carlos; Dessen, Andréa
Abstract: The type V secretion system is a macromolecular machine employed by a number of bacteria to secrete virulence factors into the environment. The human pathogen Pseudomonas aeruginosa employs the newly described type Vd secretion system to secrete a soluble variant of PlpD, a lipase of the patatin-like family synthesized as a single macromolecule that also carries a polypeptide transport-associated domain and a 16-stranded β-barrel. Here we report the crystal structure of the secreted form of PlpD in its biologically active state. PlpD displays a classical lipase α/β hydrolase fold with a catalytic site located within a highly hydrophobic channel that entraps a lipidic molecule. The active site is covered by a flexible lid, as in other lipases, indicating that this region in PlpD must modify its conformation in order for catalysis at the water–lipid interface to occur. PlpD displays phospholipase A1 activity and is able to recognize a number of phosphatidylinositols and other phosphatidyl analogs. PlpD is the first example of an active phospholipase secreted through the type V secretion system, for which there are more than 200 homologs, revealing details of the lipid destruction arsenal expressed by P. aeruginosa in order to establish infection. Graphical abstract: Highlights: PlpD is a PLA1 secreted by P. aeruginosa through the T5Vd secretion system. PlpD's compact lipase fold harbors a catalytic dyad and a trapped lipid in the cleft. PlpD broadly recognizes phosphatidyl inositols and disrupts membrane architecture.